Flipping ESP Classrooms in Hybrid Environment - Sri Yunita -; Susilawati; Yustika Nur Fajriah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2023)
The use of flipped learning in ESP (English for Specific Purposes) classes may have not been frequently portrayed. This recent study attempts to depict the implementation of a flipped learning model applied in an English for Management course. A single qualitative case study was applied. One lecturer of the English for Management course was involved in this study. The data were obtained using interviews and observations. The findings revealed that the flipped learning in the ESP class is realized in the following steps: 1) distributing materials and tasks to students, 2) providing guidance for students to discuss the materials and tasks, 3) assessing students with tests or quizzes, and 4) providing reinforcement for students in face-to-face meetings. The lecturer admitted that she encountered some challenges using flipped classrooms in ESP classes: the issues of bandwidth, students’ readiness, the lecturer's need for non-authentic materials, and the institution's policy on curriculum and facilities. Potential research in investigating ESP students’ perceptions of the use of flipped learning is strongly advised.